Methods and Means of Ensuring Information Security of Optical Systems and Communication Networks - Abdugafur Hotamov, Tulkin Sultanov (Mathematical Statistician and Engineering Applications, 2022)
The communication network will satisfy the needs of the users of services and become global, connecting them on a global scale in all sectors of the economy and helping to increase their productivity. The high efficiency of the telecommunication infrastructure is based on the existence of several standards and measurements aimed at ensuring their safe operation. However, even if standards meet the needs of the network, the increasing use of open interfaces and protocols, the greater diversity of applications and platforms, and the diversity of products that are not always adequately tested increase the potential for malicious use of communications media and networks.